Relative effectiveness of clinic and home blood pressure monitoring compared with ambulatory blood pressure monitoring in diagnosis of hypertension: systematic review. (24th June 2011) - Hodgkinson, J; Mant, J; Martin, U; Guo, B; Hobbs, F D R; Deeks, J J; Heneghan, C; Roberts, N; McManus, R J
Abstract : Objective To determine the relative accuracy of clinic measurements and home blood pressure monitoring compared with ambulatory blood pressure monitoring as a reference standard for the diagnosis of hypertension. Design Systematic review with meta-analysis with hierarchical summary receiver operating characteristic models. Methodological quality was appraised, including evidence of validation of blood pressure measurement equipment. Data sources Medline (from 1966), Embase (from 1980), Cochrane Database of Systematic Reviews, DARE, Medion, ARIF, and TRIP up to May 2010. Eligibility criteria for selecting studies Eligible studies examined diagnosis of hypertension in adults of all ages using home and/or clinic blood pressure measurement compared with those made using ambulatory monitoring that clearly defined thresholds to diagnose hypertension. Results The 20 eligible studies used various thresholds for the diagnosis of hypertension, and only seven studies (clinic) and three studies (home) could be directly compared with ambulatory monitoring. Compared with ambulatory monitoring thresholds of 135/85 mm Hg, clinic measurements over 140/90 mm Hg had mean sensitivity and specificity of 74.6% (95% confidence interval 60.7% to 84.8%) and 74.6% (47.9% to 90.4%), respectively, whereas home measurements over 135/85 mm Hg had mean sensitivity and specificity of 85.7% (78.0% to 91.0%) and 62.4% (48.0% to 75.0%). Conclusions Neither clinic nor home measurement had sufficient sensitivity or specificity to be recommended as a single diagnostic test. If ambulatory monitoring is taken as the reference standard, then treatment decisions based on clinic or home blood pressure alone might result in substantial overdiagnosis. Ambulatory monitoring before the start of lifelong drug treatment might lead to more appropriate targeting of treatment, particularly around the diagnostic threshold.